FP1-2 Implementation of duty of candor regulation within neurosurgery: a national cross-sectional survey. Issue 3 (14th February 2019) - Marcus, HJ; Sayal, P; Kitchen, N; Surajit, B; Thorne, L
Abstract : Objectives: Statutory Duty of Candor was introduced in 2014 for NHS bodies in England. Contained within the regulation were definitions regarding the threshold for what constitutes a notifiable patient safety incident. The aim of this survey was to evaluate the interpretation of these definitions by British neurosurgeons. Methods: Full members of the SBNS were electronically invited to participate in an online survey. Surgeons were presented with 15 cases and asked to decide in each one whether they would trigger the process of Duty of Candor. Cases were stratified according to their likelihood and severity. Results: In all, 106/357 (29.7%) members participated in the survey. Responses varied widely with almost no members triggering the process of Duty of Candor in cases where adverse events were likely (>10% likelihood) and required only outpatient follow up (7/106; 6.6%), and almost all members doing so in cases where adverse events were rare (<0.1% likelihood) and resulted in death (102/106; 96.2%). However, there was clear equipoise in triggering the process of Duty of Candor in cases where adverse events were unlikely (0.1%–10% likelihood) and resulted in moderate harm (38/106; 35.8%), severe harm (57/106; 53.8%), or death (49/106; 46.2%). Conclusions: There is considerable nationwide variation in the interpretation of definitions regarding the threshold for Duty of Candor; this has important implications with some providers at risk of penalties, and others unduly burdened by the associated administrative processes.